Red brick dorms, Fremont Hall, 1960 (1960)
The southwest corner and westside view of the Red Brick Dorm, Fremont Hall. The hillside and water tank are displayed in the background. To the left, the parking lot is filled with cars. The water tank is painted to look like a can of Lucky Lager. There is an article about the prank painting of the tank in the October 28, 1960 El Mustang student newspaper.